Effectiveness Menstrual Flow Monitoring Education on Menstrual Health Knowledge and Attitude Among University Students - Theresia, Theresia; Samaria, Dora; Doralita, Doralita (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Introduction: Female population 10 to 24 years old occupied almost in 30% of total female population. Female students as one of this subpopulations fall in the late adolescent age and experience a menstrual cycle. It is possible that some of them experience irregular menstrual cycles and have menstrual health issues such as premenstrual syndrome. Lack of early health education in this regard can result difficulty in early detection of menstrual abnormalities and it may develop into a serious reproductive organ disorder that continues into adulthood. Objective: This study aimed to identify the effect of menstrual flow monitoring (MFM) on the knowledge and attitudes related to menstrual health through lectures, demonstrations, and exercise methods, using the menstrual flow chart (MFC) and the menstrual calendar (MC) during sessions. Metode: This study design was quasi-experimental with only one group pretest and posttest. The subjects were 117 female students from the Teacher College of Economics Study Program who were selected by purposive sampling method. The data collected were processed using paired t-test. Data analysis revealed significant increase in the mean score of pretest to second posttest on the variables knowledge (p = 0.006) and attitude (p = 0.000). Result: This study results emphasize the need for further randomized control trial studies aimed at a larger population to disclose more relevant findings.